SPECTRUM AND OUTCOME OF PEDIATRIC RENAL DISEASES IN DR. WAHIDIN SUDIROHUSODO HOSPITAL MAKASSAR - Husein Albar (Faculty of Medicine, Hasanuddin University., 2016)
ABSTRACT Objectives: To find out thespectrum and outcome of renal diseases in children hospitalized in the pediatric ward of dr. Wahidin Sudirohusodo Hospital Makassar. Methods: We carried out a retrospective review of standard medial recordof all childrenhospitalizedinthe pediatric ward of the dr.Wahidin Sudirohusodo Hospital Makassar. Review was based on the final diagnosis on their medical records to investigate the spectrum and outcome of the pediatric renal diseasesfrom January 2009 to December 2013. Results: A total number of 9573 children were admitted during the study period, out of which 580 had renal diseases accounting for 16.5% of all pediatric admission. Age of the patients ranged from 10 months to 16.7 years with mean age of 7.39 years and majority of the cases aged 5-10 years (37.2%). Boys (55.3%)were more encountered than girls(44.7%) with a boy to girl ratio of 1.2:1 and most of the patients were in good nutritional status (48.6%). According to their final diagnosis, the commonness pediatric renal diseases in this hospital was Acute Post Streptococcal Glomerulonephritis (27.6%), followed by Nephrotic Syndrome (25.2%), Urinary Tract Infection (19.1%), and Others are Acute Glomerulonephritis (8.3%), Acute Kidney Injury(5.1%), Chronic Kidney Injury(5.0%), Wilm’s Tumor(4.7%), Hydronephrosis (3.4%), Henoch-Schoenlein Nephritis (0.9%), and Lupus Nephritis (0.7%). Length of stay of the patients was mostly in 7-14 days (46.0%) and varying from 3 up to 28 days. Mortality in pediatric patients of renal diseases in this study was 11.2% and usually in those entering the hospital with late deteriorating conditionand die before getting optimal treatment. Conclusions: In conclusion, our study shows that pediatric renal disease in the pediatric ward of dr. Wahidin Sudirohusodo Teaching Hospital Makassar accounts for 16.5%of all pediatric admission and APSGN was the commonest pediatric renal disease, followed by NS and UTI. It seems that spectrum of pediatric renal diseases in dr. Wahidin Sudirohusodo Hospital Makassar was relatively similar to that reported from other developing countries. Mortality in patients with pediatric renal diseases in our study was 11.2% and usually in those entering the hospital with late deteriorating condition and die before getting optimal treatment. Key words: Spectrum, Outcome, Renal Disease, Children, Makassar.